Duties of Justice and Transracial Adoption - Buckner, Clayton T. (My University, 2015)
Racial issues have been on display all across the United States in recent months, but one area in which racial issues are constantly being debated though not publicized is foster care. Young minority children are constantly being placed with white foster parents or adoptive parents of different cultures and socioeconomic backgrounds. Many sociologists, such as W.E.B. Du Bois, have found that placing minority children in a different culture creates a double consciousness and harms the culture of their biological parents. However, there are several contemporary philosophers, such as Elizabeth Anderson, who argue that integration must be taking place in every social arena, including the family, in order to solve man social problems, especially those involving race. This research project will work through philosophical, sociological, and legal literature in order to answer the following questions: is the interracial adoption of minority children by white parents in the best interest of the children? Should interracial adoption be encouraged because it leads to greater integration within society? Is a harm done to African American culture when African American children are raised by parents of a different race? These questions will be researched by looking at adoption policies, empirical data, and scholarly writings, especially Elizabeth Anderson’s The Imperative of Integration and Tommie Shelby’s “Integration, Inequality, and Imperatives of Justice: A Review Essay”. Following the review of these articles, this paper will argue that adoptive parents have a duty to seek out transracial adoptions in order to counter the harms of segregation with active steps toward a more integrated society.